Population dynamics and stock status of Rastrelliger kanagurta in the Marudu Bay, Sabah - Jaafar, Siti Noor Fatinah (2013)
An investigation of the population dynamics of Indian mackerel, Rastrelliger kanagurta (Cuvier, 1816) in the Marudu Bay, Sabah, Malaysia was carried out from January 2013 to September 2013. The overall relationship between total length and body weight was estimated as W= 0.006TL3.215 or Log W= 3.215 Log TL – 0.006 (R2 = 0.946).Monthly length frequency data of R. kanagurta were analyzed by FiSAT software to evaluate the mortality rates and its exploitation level. Asymptotic length (L) and growth co-efficient (K) were estimated at 27.83 cm and 1.50 yr-1, respectively. The growth performance index (φ') was calculated as 3.065. Total mortality (Z), natural mortality (M) and fishing mortality (F) was calculated at 4.44 yr-1, 2.46 yr-1 and 1.98 yr-1. The size for R. kanagurta at first recruitment is 11.5 cm. The exploitation level (E) of R. kanagurta was calculated at 0.45. The exploitation level was below the optimum level of exploitation (E = 0.50). The stock of R. kanagurta was found to be under exploited in the Marudu Bay.